(untitled) (Jurnal Pendidikan Fisika, 2020)
This research is a Pre-Experimental study using the One-Group Pretest-Posttest Design which aims to find out: (1) the magnitude of physics learning outcomes of XI MIPA SMA N 8 Gowa students before and after applying the problem based learning model (2) differences in physics learning outcomes of students class XI MIPA SMA N 8 Gowa before and after the problem based learning model is applied. The population in this study were students of class XI MIPA of SMA N 8 Gowa, amounting to 136 students divided into 4 classes, the study sample was taken randomly with a simple random sampling technique of 1 class, namely XI MIPA. The research instrument used was a physics learning achievement test instrument in the form of multiple choice of 27 numbers that met valid criteria.The data analysis technique used in this study is to use descriptive tests that are useful to test average scores, standard deviation and inferential test that are useful for testing normality and hypothesis testing. From the results of the study it can be concluded that: (1) The physics learning outcomes of students before applying the problem based learning model to students of class XI MIPA SMA Negeri 8 Gowa in the 2019/2020 school year the average score obtained was 12,82; (2) the physics learning outcomes of students after applying the problem based learning model to students of class XI MIPA SMA Negeri 8 Gowa in the 2019/2020 school year the average score obtained was 17,15; (3) There are differences in students’ physics learning outcomes before and after the problem based learning model is applied to the students of Class XI MIPA in SMA Negeri 8 Gowa in the academic year 2019/2020. So it can be concluded that the problem based learning model can be applied toimprove student learning outcomes.